First: replace "x+h" with the x-variable in the function...
F(x+h) = 3(x+h) + 4
F(x+h) = 3x + 3h + 4
Sec: take the result "3x + 3h + 4" and subtract the original function...
[(3x + 3h + 4) - (3x + 4)]/h
Third: solve the expression, eliminate parenthesis > distribute the negative sign with the terms in the 2nd parenthesis
[3x + 3h + 4 - 3x - 4]/h
*Combine "like" terms...
[3x - 3x + 3h + 4 - 4]/h
3h/h
Cancel "like" terms...
= 3
2007-01-27 06:39:31
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
0⤊
1⤋
F(x) = 3x + 4
Let's do this one at a time. Before we solve the big formula, let's solve the smaller one first.
F(x + h) = 3(x + h) + 4, so
F(x + h) = 3x + 3h + 4
Now, all we have to do is plug this into our big formula.
[F(x + h) - F(x)]/h = [ [3x + 3h + 4] - [3x + 4] ] / h
First, let's distribute the minus sign.
[F(x + h) - F(x)]/h = [ 3x + 3h + 4 - 3x - 4 ] / h
[F(x + h) - F(x)]/h = [3h] / h
Cancelling out the h terms, we get 3.
You are correct.
2007-01-27 02:30:39
·
answer #2
·
answered by Puggy 7
·
1⤊
0⤋
F(x) = 3x + 4
so
F(x + h) = 3(x + h) + 4
F(x + h) = 3x + 3h + 4
so
[F(x + h) - F(x)]/h
= [ (3x + 3h + 4) - (3x + 4) ] / h
= [ 3x + 3h + 4 - 3x - 4 ] / h
hence we get
[F(x + h) - F(x)]/h = 3h / h
hence we get 3 after cancelling h in numerator and denomenator.
so it is CORRECT to say that
[F(x + h) - F(x)]/h = 3.
2007-01-27 02:38:48
·
answer #3
·
answered by rajeev_iit2 3
·
1⤊
1⤋
yes, it is
Drudge: Are you a student in Junior High or Middle School? Or are you making up the lessons to get a high school diploma?
2007-01-27 02:44:18
·
answer #4
·
answered by abc 2
·
0⤊
2⤋
Puggy did a good job. He's right.(or she?)
2007-01-27 02:40:40
·
answer #5
·
answered by Mila S 4
·
0⤊
1⤋